Analyzing EFL learners’ demotivating factors in blended learning context - Wenjing Zhou; Yan Zhan; Esther Jawing (Frontiers Media S.A., 2023)
In second language and foreign language learning, demotivation in learning is a common occurrence. Almost all previous studies on learners’ demotivation focused on traditional classroom learning environment rather than blended learning setting. This paper investigates learner perceptions of demotivating factors for Chinese EFL college students in blended learning context. 272 college sophomores with varied majors from a university in Mid-East China took part in a questionnaire survey. The questionnaire, consisted of 34 4-point Likert type items about learners’ demotivation in a blended EFL learning environment, was adapted from Kikuchi’s demotivation questionnaire and Xie’s LPDS (Learner Perceptions of Demotivator Scale). An exploratory factor analysis was performed to explore the factor structure of the questionnaire items. Then mean scores of items loading on each factor were calculated and independent samples t-test analysis was adopted to examine the differences of demotivating factors between different groups of participants. Five demotivating factors from the questionnaire were extracted. The findings reveal a newly discovered factor: learners’ lack of self-discipline in online learning. The paper indicates that there is no significant difference of these five demotivating factors between male and female learners, and between rural and urban learners. Whereas less motivated learners perceive four among the five factors to be more demotivating than more motivated learners.